African solutions to African problems: An assessment of the African Union (AU)'s policy implementation for peace and security in the Democratic Republic of Congo (DRC) since 2004 - Yuksel, Aysegul (African Studies, 2023)
Despite the historical significance of states in Africa gaining political independence since the 1950s, the continent has struggled with the challenges of sustaining security and peace. African leaders, who set out with the ideals of the iconic Nkrumah's ‘Pan-Africanism' of the 1950s, as committed to in the launching of the Organisation of African Unity (OAU) in 1963, sought permanent solutions to problems rooted in this decolonial ideal when they founded the subsequent African Union (AU) in 2002. The stated aim of the AU was to create peace, security, and stability in Africa. Accordingly, the slogan ‘African solutions to African problems' is closely linked to Pan-Africanism as a decolonial philosophy and driving force that became a policy objective. The African Peace and Security Architecture (APSA), implemented in 2002 at the founding of the AU, was established as a mechanism to obtain this objective. The AU has undertaken to take a leading role and responsibility in addressing violent conflicts in Africa as the root issue lies in the historical context that African problems are neither caused nor continued by sovereign African agencies; the point is historically, politically, and economically more complex. Hence, the stated ideal of the aphorism ‘African solutions to African problems' can only be meaningfully attained if the mechanisms to achieve peace and security are situated within sovereign African agencies and cultural political philosophies – the complexities of the global and post-colonial political and economic context notwithstanding. This mini-thesis critically engages the stated Africa-centred decolonial aspiration and approach for sovereignty and asks, therefore, to what extent the AU has succeeded in applying its sovereign agency in achieving ‘African solutions' designed for peace in the case study of the Democratic Republic of Congo (DRC) since 2004.